2021
DOI: 10.1093/intqhc/mzab093
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to evidence-based practice implementation in physiotherapy: a systematic review and meta-analysis

Abstract: Background To review and meta-analyse the evidence about the prevalence of barriers to evidence-based practice (EBP) reported in physiotherapy. Methods Two independent investigators conducted an extensive electronic search in EMBASE, PubMed, Scopus, Web of Science and CINAHL databases from their inception to July 2020 and included the retrieved articles if they investigated barriers to EBP among physiotherapy professionals. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
61
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 65 publications
7
61
0
2
Order By: Relevance
“…Several studies have investigated the effectiveness of EBP learning theories for undergraduate students; however, there is no conclusive evidence for the most effective theory for developing and supporting EBP capability [ 5 , 6 ]. Although cumulative evidence indicates that physiotherapists have a positive attitude regarding EBP and its implementation, further education and training are required in this field [ 3 , 7 , 8 ]. A recent systematic review (2021) identified barriers to implementing EBP in physiotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the effectiveness of EBP learning theories for undergraduate students; however, there is no conclusive evidence for the most effective theory for developing and supporting EBP capability [ 5 , 6 ]. Although cumulative evidence indicates that physiotherapists have a positive attitude regarding EBP and its implementation, further education and training are required in this field [ 3 , 7 , 8 ]. A recent systematic review (2021) identified barriers to implementing EBP in physiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review (2021) identified barriers to implementing EBP in physiotherapy. In addition to the language barrier, commonly reported barriers include lack of time to discover and appraise evidence; skills to search, identify, and apply the best evidence; and access to the evidence [ 8 ]. Further barriers include a low perception of EBP, lack of interest or support from employers, statistical understanding [ 7 ], and educational barriers [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a restricted implementation of recommended interventions can contribute toward avoidable disabilities and indeed harm ( 77 ), guideline implementation is relevant for any health condition ( 78 , 79 ) and for any healthcare profession ( 80 , 81 ). Barriers to guideline-compliant practice have been found to be individual, external, or guideline related, and these have been studied both in general ( 82 84 ) and in specific circumstances ( 85 , 86 ). Knowledge of existing barriers, as well as the use of theoretical underpinning of behavioral change, is recommended to develop promising strategies for addressing the factors that determine guideline adherence ( 87 ).…”
Section: Discussionmentioning
confidence: 99%
“…Structural factors represent major barriers to evidence implementation for most health professions 64 , 65 , 66 , 67 ; this was no exception for CM practitioners. Consistent with other professions, 64 , 65 , 66 , 67 ‘availability’ of time and ‘availability’ of clinical evidence were amongst the most frequently reported structural barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Structural factors represent major barriers to evidence implementation for most health professions 64 , 65 , 66 , 67 ; this was no exception for CM practitioners. Consistent with other professions, 64 , 65 , 66 , 67 ‘availability’ of time and ‘availability’ of clinical evidence were amongst the most frequently reported structural barriers. Notwithstanding, few studies in this review reported enablers specifically targeting this barrier (with suggestions limited to supporting the generation of CM evidence and CM guidelines).…”
Section: Discussionmentioning
confidence: 99%